Motaain Boundaries: Between State Sovereignty and Indigenous People - Alfridus Saverius Daniael DARI; Ananias Riyoan Philip JACOB; Frans W. MUSKANAN; Yeftha Y. SABAAT (International Journal of Environmental, Sustainability, and Social Science, 2023)
The border issue has always been a problem that continues to be debated by every country. One of the issues that are important but rarely highlighted is social issues that involve relations and interactions between people in bordering countries. As happened in Motaain, the border between Indonesia and Timor Leste. The separation of the two regions after the 1999 East Timor Popular Consultation resulted in various traditions and indigenous cultures being transformed into cross-border cultures. This transformation occurred because previously the two boundary communities came from the same culture. This can be explored from three aspects: historical, cultural, and genealogical ties. Separation of the country does not eliminate cultural relations and interactions even though they have different citizenship statuses. Cross-border culture creates harmonization of border communities so that horizontal conflicts at the border can be minimized. However, cross-border culture needs state control because it risks territorial sovereignty, as well as having loopholes for certain elements to exploit to create transnational violations and crimes. This issue has become the concern of the two countries in controlling people across the border. State policies that negotiate with culture as well as negate previous opinions that see the state as the sole actor in managing boundaries. The state does not have to control borders with power, but it can also be done by giving space for its citizens to interpret borders with cross-border culture